Exploring Intersections of Race and Disability in the Context of Canadian Employment Support Systems Through the Experiences of Job Seekers/Workers, Employers, and Service Providers. - Grewal, Eakam; Durocher, Evelyne; Premji, Stephanie; Gewurtz, Rebecca (Journal of Occupational Rehabilitation, 2026)
Purpose: Racism and ableism have impacts at individual and organizational levels and can produce and reproduce inequities and injustices in diverse contexts. However, their intersection remains largely unexamined in the provision of employment supports. The objective of this qualitative study is to identify barriers and facilitators within employment supports to seek strategies to improve the employment outcomes of racialized disabled job seekers and workers and address gaps faced by service providers and employers. Methods: This study used interpretive description (Thorne S. Interpretive description: Qualitative research for applied practice; 2016.). Four racialized disabled job seekers and workers, two employers and four service providers from Canada participated in semi-structured interviews. Thematic analysis (Braun and Clarke in Qual Res Psychol 3:77–101, 2006) was used to analyze the data. Findings: Five core themes were identified: (1) managing intersectional confusion; (2) employer education; (3) contextual barriers; (4) client-service provider relationships; and (5) urgency for solutions. Conclusion: This study provides grounding evidence about common concerns and barriers within existing employment support systems and can assist policymakers and service providers to better understand the complex and nuanced lived experiences of racialized disabled job seekers and workers.